Improvement of polyurea/weaved carbon fibre composite mechanical properties - Kwek, Yorick Yu Li (Nanyang Technological University, 2021)
Carbon fibre is known to have a high strength to weight ratio, making it an ideal material for protective purpose. Carbon fibre composite plates are commonly used as a spall protection layer in armour vehicles and body armour. It serves as the last line of defence to protect the vehicle's occupants or the wearer from fragments caused by the steel plates' spallation. Currently, carbon fibre weaves are generally made into plates using epoxy as the matrix. Epoxy has relatively low elongation, ranging from 1 – 20%, compared with polyurea, which can elongate up to 500%. This mechanical property of polyurea makes it a potential candidate for energy absorption material. Therefore, by replacing the matrix with polyurea, carbon fibre composite plates' energy absorption capability can be increased significantly compared to the more conventional epoxy carbon fibre composite. The aim of this final year project proposes a viable fabrication process for making reinforced polyurea carbon fibre composites and understand their mechanical properties under different loading conditions. The polyurea matrix was made by mixing isocyanate and diamine, and the sample carbon fibre composite was prepared through compression moulding, hand lay-up hybrid process. Instron tensile and compression quasi-static tests were conducted to examine the mechanical properties of the respective composite samples. Hence, to study the high strain rate compression properties similar to a projectile penetration, Split Hopkinson compression bar tests were performed. Lastly, an optical microscope was used to examine the resin infiltration and fracture failure within the various samples.